Ultrahigh field imaging of myelin disease models: Toward specific markers of myelin integrity?. Issue 13 (4th January 2019) - Petiet, Alexandra; Adanyeguh, Isaac; Aigrot, Marie‐Stéphane; Poirion, Emilie; Nait‐Oumesmar, Brahim; Santin, Mathieu; Stankoff, Bruno
Abstract: Specific magnetic resonance imaging (MRI) markers of myelin are critical for the evaluation and development of regenerative therapies for demyelinating diseases. Several MRI methods have been developed for myelin imaging, based either on acquisition schemes or on mathematical modeling of the signal. They generally showed good sensitivity but validation for specificity toward myelin is still warranted to allow a reliable interpretation in an in vivo complex pathological environment. Experimental models of dys−/demyelination are characterized by various levels of myelin disorders, axonal damage, gliosis and inflammation, and offer the opportunity for powerful correlative studies between imaging metrics and histology. Here, we review how ultrahigh field MRI markers have been correlated with histology in these models and provide insights into the trends for future developments of MRI tools in human myelin diseases. To this end, we present the biophysical basis of the main MRI methods for myelin imaging based on T1, T2, water diffusion, and magnetization transfer signal, the characteristics of animal models used and the outcomes of histological validations. To date such studies are limited, and demonstrate partial correlations with immunohistochemical and electron microscopy measures of myelin. These MRI metrics also often correlate with axons, glial, or inflammatory cells in models where axonal degeneration or inflammation occur as potential confounding factors. Therefore, the MRI markers' specificity for myelin is still perfectible and future developments should improve mathematical modeling of the MR signal based on more complex systems or provide multimodal approaches to better disentangle the biological processes underlying the MRI metrics. Abstract : T2 ‐weighted images shows demyelination in the corpus callosum and external capsule (EC) after 12 weeks of cuprizone diet as a hyper‐intensity (left, bottom). Comparing parametric T2 values, a faster recovery was detected in animals treated with the promyelinating drug TFA‐12 (right).